Konsep Pembangunan Pusat Kegiatan Desa Canden - Pratama, Yohanes Mario (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
This community service is carried out in order to assist the community in developing the potential of the village from various aspects of community life. This community service was carried out in Canden Village, Bantul Regency, Yogyakarta Special Region Province. Canden village has artistic potential such as ketoprak, jatilan, srandul, sholawatan, karawitan, sinden, and wayang kulit. In this service, a work program was created in order to develop the potential of the village in the form of a building program or open space that can be used as a center for Canden Village activities, both for art performances and meetings. The data collection process is carried out using secondary data such as looking at the geographical conditions of the village, village facilities and infrastructure, village access, village facilities, what potential the village has that needs to be developed. The result of this stage is that there is an open space design that can be used for cultural and artistic performances as well as village meetings and meetings. This open space is expected to be able to attract the attention of tourists to visit Canden Village and increase community productivity in Canden Village.